A Journey Towards the Meaningful Inclusion of Children in the Church of the Nazarene. (July 2016) - Jara, Reverend Trino
Throughout the history of Christianity, children have often been overlooked in the life of the Church. Since its beginning, the Church of the Nazarene International has gone through a journey from ignoring the value of children, to ministry engaged in permanent advocating on behalf of children and youth. As a Christian, Holiness, and Missional people, Nazarenes around the world have developed their perspective on children and youth through the establishment of specific ministries that include children and youth in their core values, and by emphasis on intergenerational connections and making historical changes to their procedures manual. All of this has been critical to the meaningful inclusion of children in the active life of the church. Today the Church of the Nazarene together with Nazarene Compassionate Ministries are actively advocating and educating new generations of pastors and leaders to better understand the importance of children and youth in the life of the church.